Literature review : trends in community service delivery systems and community organisation forms - Queensland Community Housing Coalition; Queensland Council of Social Service; University of Queensland. Community Service & Research Centre (Brisbane, Qld : Queensland Community Housing Coalition and Queensland Council of Social Service Inc., 2005)
This paper seeks to examine the key trends in community service delivery systems and community service organisation forms and models, in light of market reforms that have occurred in recent years. The development of markets, or more accurately quasi-markets in the community service sector has resulted in a range of impacts on government, private and nonprofit organisations alike. Such impacts have required both the community service sector and individual organisations to respond to this new environment.
Title from title screen (viewed on Sept. 12, 2007)
Mode of access: Internet. Available at: http://www.uq.edu.au/boilerhouse/index.html?page=33708
Selected for archiving for the Pandora Archive
Keywords: Human services; Social service